The prone bridge test: Performance, validity, and reliability among older and younger adults - Bohannon, Richard W; Steffl, Michal; Glenney, Susan S; Green, Michelle; Cashwell, Leah; Prajerová, Květa; Bunn, Jennifer (Journal of bodywork and movement therapies, 2018)
INTRODUCTION: The prone bridge maneuver, or plank, has been viewed as a potential alternative to curl-ups for assessing trunk muscle performance. The purpose of this study was to assess prone bridge test performance, validity, and reliability among younger and older adults. METHOD: Sixty younger (20-35 years old) and 60 older (60-79 years old) participants completed this study. Groups were evenly divided by sex. Participants completed surveys regarding physical activity and abdominal exercise participation. Height, weight, body mass index (BMI), and waist circumference were measured. On two occasions, 5-9 days apart, participants held a prone bridge until volitional exhaustion or until repeated technique failure. Validity was examined using data from the first session: convergent validity by calculating correlations between survey responses, anthropometrics, and prone bridge time, known groups validity by using an ANOVA comparing bridge times of younger and older adults and of men and women. Test-retest reliability was examined by using a paired t-test to compare prone bridge times for Session1 and Session 2. Furthermore, an intraclass correlation coefficient (ICC) was used to characterize relative reliability and minimal detectable change (MDC95%) was used to describe absolute reliability. RESULTS: The mean prone bridge time was 145.3 ± 71.5 s, and was positively correlated with physical activity participation (p ≤ 0.001) and negatively correlated with BMI and waist circumference (p ≤ 0.003). Younger participants had significantly longer plank times than older participants (p = 0.003). The ICC between testing sessions was 0.915. CONCLUSION: The prone bridge test is a valid and reliable measure for evaluating abdominal performance in both younger and older adults.
Keywords: Abdominal Muscles; dospělí; tělesné váhy a míry; pronační poloha; index tělesné hmotnosti; břišní svaly; Humans; lidé středního věku; Middle Aged; Muscle Fatigue; Young Adult; reprodukovatelnost výsledků; mladý dospělý; svalová únava; Body Mass Index; mužské pohlaví; Physical Therapy Modalities; Aging; Muscle Strength; techniky fyzikální terapie; Adult; Prone Position; Body Weights and Measures; ženské pohlaví; svalová síla; lidé; Reproducibility of Results; Aged; senioři; Male; stárnutí; Female